The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pd.2944
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial translucency at 11–13 weeks of gestation: prospective evaluation and reproducibility of measurements

Abstract: The IT increases linearly with increasing crown-rump length and seems to be of value in the first-trimester detection of spina bifida. It is easy to identify and measure and shows excellent intra-observer and inter-observer reproducibility measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 15 publications
(25 reference statements)
4
33
1
2
Order By: Relevance
“…In our prospective study, after specific training for intracranial translucency visualization, 10 nonphysician sonographers were able to obtain adequate images of the posterior brain structures, with intracranial translucency visualization in 96% of normal fetuses at the time of the 11‐ to 13‐week nuchal translucency ultrasound scan. This rate is comparable to the intracranial translucency visualization rates of 97% to 100% reported by 2 recent prospective studies in which the 11‐ to 13‐week scans were performed by highly skilled obstetricians with considerable experience in first‐trimester scanning 6 , 14 . Our study suggests that it is feasible to introduce the intracranial translucency technique in conjunction with nuchal translucency screening by adequately trained nonphysician sonographers at 11 to 13 weeks' gestation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our prospective study, after specific training for intracranial translucency visualization, 10 nonphysician sonographers were able to obtain adequate images of the posterior brain structures, with intracranial translucency visualization in 96% of normal fetuses at the time of the 11‐ to 13‐week nuchal translucency ultrasound scan. This rate is comparable to the intracranial translucency visualization rates of 97% to 100% reported by 2 recent prospective studies in which the 11‐ to 13‐week scans were performed by highly skilled obstetricians with considerable experience in first‐trimester scanning 6 , 14 . Our study suggests that it is feasible to introduce the intracranial translucency technique in conjunction with nuchal translucency screening by adequately trained nonphysician sonographers at 11 to 13 weeks' gestation.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have reported on measurement of the anteroposterior diameter of intracranial translucency and reference ranges in normal fetuses, demonstrating that intracranial translucency increases linearly with increasing crown‐rump length 1 , 6 , 16 . Manual measurements of intracranial translucency have been shown to be reproducible 6 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, five prospective studies looking at different posterior fossa components, including the IT as one of the components, have been reported . The largest is a multicentre prospective study by Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study including 990 fetuses Adiego et al reported that the mean IT anteroposterior diameter was 1.8 mm (range 0.8-3.1) [14] . In another study including 201 singleton fetuses median IT value for the first trimester was 1.7 mm (range 1-2.4) [15] .…”
Section: Discussionmentioning
confidence: 99%